Application of UV/chlorine pretreatment for controlling ultrafiltration (UF) membrane fouling caused by different natural organic fractions. (January 2021) - Wan, Ying; Xie, Pengchao; Wang, Zongping; Wang, Jingwen; Ding, Jiaqi; Dewil, Raf; Van der Bruggen, Bart
Abstract: In this study, the effects of UV/chlorine pretreatment on ultrafiltration (UF) membrane fouling derived from different fractions of natural organic matter (NOM) were studied and compared. Three model organic compounds including humic acid (HA), sodium alginate (SA) and bovine serum albumin (BSA) were employed to represent different NOM fractions in natural surface water. The results suggest that membrane fouling induced from HA, SA and HA-SA-BSA mixture could be effectively mitigated by UV/chlorine pretreatment, which could be further improved by increasing the chlorine dose. Although UV irradiation alone severely aggravated BSA fouling, the addition of chlorine (0.0625 mM) to the pretreatment process could effectively avoid the fouling. The alleviation of membrane fouling is primarily ascribed to the reduction of molecular weight (MW) of organic compounds, and the decomposition of unsaturated organic species, thereby reducing the accumulation of organics on the membrane surface and pores. This is confirmed by the reduction of UV254 and fluorescent components in the feed solution and the increase of DOC in the permeate after UV/chlorine pretreatment. Membrane fouling during the filtration of untreated HA, SA, and HA-SA-BSA mixture was occupied by cake filtration and intermediate pore blocking, while UV/chlorine pretreatment led to the exacerbation of pore blocking at the initial filtration stage. The initial fouling mechanism of untreated BSA was mainly governed by complete blocking, which shifted to intermediate pore blocking after UV/chlorine pretreatment. Graphical abstract: Image 1 Highlights: UV/chlorine pretreatment was used to control UF fouling by different NOM fractions. UV/chlorine pretreatment effectively alleviated membrane fouling. The destruction of organic compounds accounted for the fouling mitigation. Effects of UV/chlorine pretreatment on fouling mechanism was compared and studied.